Bioenergy production from sunflower husk in Ukraine: potential and necessary investments - Horák, Jakub; Bilan, Yuriy; Dankevych, Andrii; Nitsenko, Vitalii; Kucher, Anatolii; Streimikiene, Dalia (Journal of Business Economics and Management, 2023)
Sunflower is a strategic crop in the agriculture of Ukraine as it is important for food and energy production. Recently the processing of secondary products, solving the issues of waste disposal and improving the environment have been paid much attention. This is an example of a cyclic economy, as during the production of oil from sunflowers, their husk can be used for energy production. The ash obtained by burning husk is a valuable complex mineral fertilizer and can be further applied as ecological fertilizer. The aim of this article is to assess the energy and investment potential for sunflowers as an internal reserve for increasing production efficiency and reducing carbon dioxide emissions. In particular, the equivalents of energy substitution of sunflower husks for energy costs at fat-and-oil enterprises, the reduction of carbon dioxide emissions are estimated. A generalized scheme for the production of electricity from sunflower husks is considered. In particular, the use of ash from sunflower husks as a fertilizer is described. The research has shown that the sunflower husks available in Ukraine can be used more efficiently to produce electricity. Therefore policy recommendations were developed based on a study conducted.